The effects of the Media Instruction Program (MIP) modules on the information literacy skills of the Ateneo de Manila Grade School grade five students - Dela Cruz, Maria Victoria E. (School of Library and Information Studies, University of the Philippines Diliman, 2014)
"The study was conducted to measure the effectiveness of the Media Instruction Program (MIP) of the Ateneo de Manila Grade School through the MIP Modules taught to selected Grade Five students enrolled for SY 2014-2015. Students were given a pre-test at the beginning of SY 2014-2015 to measure their information literacy skills. After attending MIP sessions at the Katigbak Educational Media Center (KEMC) they were given post-test to measure the difference in their pre-test and post-test scores. It was hypothesized that there is a significant difference in the pre-test and the post-test information literacy skills of Grade Five students after they have been exposed to the Media Instruction Program. The study consisted of two parts. The first part was when the researcher formulated the modules while the second part was when the modules were implemented through the MIP sessions. In the first phase, the data were gathered from the guidance counselors, librarians, experts in the field of librarianship, library standards, and various literatures in library instruction program. Likewise, the data in the second phase of the study were gathered through the administered tests before and after the students were exposed to the Media Instruction Program sessions. The tests were collated, tallied ad submitted to correlation analysis and two-tailed t-test. The study determined that there was a positive correlation between the pre-test and post-test scores. The result of the T-test showed that there is a significant positive difference between the pre-test and post-test scores of the Grade Five students. It indicates that the Media Instruction Program modules had a very significant positive impact on the test scores of the Ateneo de Manila Grade School Grade Five students. Majority of the Grade Five students have shown improvement in their post-test scores as compared to their pre-test scores. There was an observed increase and significant improvement in the test scores of students. There was also a significant difference in the pre-test and post-test information literacy skills of Grade Five students after they have been exposed to Media Instruction Program. Based on the findings of the study, it is recommended that the librarians should have a periodic review and implementation of the Media Instruction Program content and lesson plans. The librarian should continuously update themselves professionally and collaborate with the English teachers and among the librarians regularly to come up with a well-defined Media Instruction Program. Although the study revealed that the MIP had a very significant positive impact on the test scores of students, there is still a need to consider more creative measures of promoting new acquisitions aside from having the new titles displayed in the library. It is recommended that the developed MIP modules be used by other school librarians and other libraries after incorporating possible revisions to improve the lessons."